Early Menarche and its Possible Predictors: A Cross-Sectional Study in Southwestern Region of Karnataka, India - Sowjanya T; Balakrishna Nagalla (Medsci Publications, 2024)
Background: Early menarche has emerged as a significant global concern due to its myriad health implications. Divergent findings characterize existing research on its determinants, prompting the necessity for this study to elucidate the discordance among them and to broaden the spectrum of predictors of early menarche. The primary objective of this study is to determine the mean menarcheal age and to study the influence of various factors, including socio-demographic characteristics, body mass index (BMI), and lifestyle habits, on the onset of menarche in our study population. Methodology: This was a questionnaire-based cross-sectional study carried out in the southwestern region of Karnataka between 2016 and 2017. A total of 700 high school girls aged between 14 and 16 years were recruited for the study via a simple random sampling technique. Results: The mean menarcheal age was found to be 12.67 ± 1.19 years, with 33% experiencing it before the age of 12. Factors accelerating menarche included high BMI, excessive exposure to audio-visual media, lack of exercise, non-vegetarian diet, and late sleeping habits, as determined by stepwise logistic regression analysis. Conclusions: Findings emphasize the significance of monitoring menarcheal trends and identifying modifiable factors influencing its onset. There is a need for educational programs focusing on the holistic health of girls.